2022
DOI: 10.1158/1078-0432.ccr-22-2046
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of ONCOS-102 and Pembrolizumab: Remodeling of the Tumor Microenvironment and Clinical Outcomes in Anti–PD-1–Resistant Advanced Melanoma

Abstract: Purpose: Intratumoral oncolytic virotherapy may overcome anti–PD(L)-1 resistance by triggering pro-inflammatory remodeling of the tumor microenvironment. This pilot study investigated ONCOS-102 (oncolytic adenovirus expressing GM-CSF) plus anti–programmed cell death protein 1 (PD)-1 therapy in anti–PD-1–resistant melanoma. Experimental Design: Patients with advanced melanoma progressing after prior PD-1 blockade received intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…It has been reported that cancer-associated Macrophage play a key role in tumor progression, angiogenesis, invasion and recruitment of immunosuppressive cells ( Samain and Sanz-Moreno, 2020 ). Persistent immune-related gene expression and T-cell penetration were associated with clinical benefit in SKCM patients ( Shoushtari et al, 2022 ). The infiltrating levels of various effector T cells, such as CD4 + and CD8 + T, were significantly higher in the immune-high group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cancer-associated Macrophage play a key role in tumor progression, angiogenesis, invasion and recruitment of immunosuppressive cells ( Samain and Sanz-Moreno, 2020 ). Persistent immune-related gene expression and T-cell penetration were associated with clinical benefit in SKCM patients ( Shoushtari et al, 2022 ). The infiltrating levels of various effector T cells, such as CD4 + and CD8 + T, were significantly higher in the immune-high group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, these regimens are only effective for a subset of patients, with others showing only a limited response or response failure, especially in the advanced stages ( 23 , 24 ). Furthermore, most patients with advanced melanoma do not respond to ICI therapy due to primary or acquired drug tolerance ( 22 , 25 ). Combining anti- CTLA4 and anti- PD - 1 checkpoint inhibitors to enhance antitumor immune reactions, or ICIs combined with intratumoral oncolytic virotherapy, may trigger pro-inflammatory rebuilding of the TME to overcome anti- PD - L1 resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma oncolysis caused by oncolytic adenovirus can remodel the tumor microenvironment to enhance the efficacy of PD-1 blockade therapy; for example, by leading to the polarization of pro-inflammatory M1-type macrophages, in turn stimulating the proliferation and cytokine production of CD4 + and CD8 + T cells 93 ;…”
Section: Oncolytic and Non-oncolytic Adenovirusmentioning
confidence: 99%
“…Melanoma oncolysis caused by oncolytic adenovirus can remodel the tumor microenvironment to enhance the efficacy of PD‐1 blockade therapy; for example, by leading to the polarization of pro‐inflammatory M1‐type macrophages, in turn stimulating the proliferation and cytokine production of CD4 + and CD8 + T cells 93 ; and by increasing infiltration of various effector immune cells and APCs in both local and distant tumors and decreasing M2‐type macrophages in the spleen 94,95 …”
Section: Combination Therapiesmentioning
confidence: 99%